Visibilidade e uso do portal de periódicos da CAPES: disseminação da informação nos cursos de música, teatro e artes visuais da Universidade Federal do Pará - PEREIRA, Dalyta Bruna Bastos (2017)
Study on portals like and your source of information dissemination for scientific research, with the overall objective to analyze the visibility and use of the Capes Journal Portal courses in music, theater and Visual Arts of the UFPA. Was with bibliographical survey of the literature on the scientific communication, dissemination of information, the importance of scientific journals and the Capes Journal Portal. It is characterized as a search field, with questionnaires for data collection. The corpus of this research consisted of three courses at the Federal University of Pará: Music Theatre and Visual Arts. Among the results showed low use of CAPES Portal courses in music, theater and Visual Arts of the Federal University of Pará, due to the ignorance of this important instrument of dissemination of scientific information. The research points to the need to be carried out other forms of dissemination of the Portal in the courses investigated, considering that in the Portal many can be accessed. In conclusion, it is observed that the students of these courses mostly do not know and do not use the Portal of CAPES journals.